2011
DOI: 10.1584/jpestics.g10-49
|View full text |Cite
|
Sign up to set email alerts
|

Effect of formulations and treatment methods of nursery boxes applied with insecticide on the behavior of imidacloprid in rice paddy fields

Abstract: The behavior of imidacloprid was investigated in two paddy plots with conventional release granular formulation and controlled release granular formulation corresponding to before transplanting (BT) treatment and at sowing (AS) treatment (14 days before transplanting) in nursery boxes, respectively. The maximum concentrations of imidacloprid were 30.2 mg/l and 3.0 mg/l in paddy water at 0.5 days after transplanting (DAT), and 278.4 mg/kg and 81.4 mg/kg in 1cm paddy surface soil at 1 DAT for BT and AS treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(71 citation statements)
references
References 35 publications
7
61
0
Order By: Relevance
“…In a similar study, uyet et al 1) observed that the average water depths were 4.2±1.9 cm and 3.9±1.9 cm in two studied plots, and the calculated input and output were about 1.2 cm/day and 1.1 cm/day, respectively. Figure 1 shows that the water balance for the actual paddy plot and in MPL of both BT and AS treatments were identical, indicating the acceptable accuracy and precision of these MPL experiments for simulating the hydrological response of an actual paddy plot.…”
Section: Water Management and Environmental Conditions In Mplmentioning
confidence: 58%
See 4 more Smart Citations
“…In a similar study, uyet et al 1) observed that the average water depths were 4.2±1.9 cm and 3.9±1.9 cm in two studied plots, and the calculated input and output were about 1.2 cm/day and 1.1 cm/day, respectively. Figure 1 shows that the water balance for the actual paddy plot and in MPL of both BT and AS treatments were identical, indicating the acceptable accuracy and precision of these MPL experiments for simulating the hydrological response of an actual paddy plot.…”
Section: Water Management and Environmental Conditions In Mplmentioning
confidence: 58%
“…For AS treatment, the granules are applied with soil incorporation or sandwiched together with rice seeds in soil about 14 days before transplanting. 1) e monitoring of imidacloprid in paddy water and 1-cm surface soil of experimental paddy plots has been reported in previous publications; [1][2][3] however, the residue and distribution of imidacloprid in a deeper soil layer of paddy soil has not been reported. e environmental fate of imidacloprid is rather inconsistent depending on various factors, including environmental and eld conditions, 4) and water balance has been reported as a major factor that in uences the dissipation of pesticide in rice paddy water.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations